The space : a guide for educators - Hare, Rebecca Louise; Dillon, Robert (Irvine, CA : EdTechTeam Press, 2016)
"Space is a beautifully designed book that respects that reading and learning can happen in a visually appealing way. Hare and Dillon walk educators through a series of questions and ideas on how learning spaces can support collaboration, creation, showcasing learning, and a learner's need for quiet. In addition to nudging thinking forward, Space provides practical design tips and uses images and testimonials for hacking learning spaces on a realistic budget. This book is designed to motivate, grow capacity, and energize educators to begin shifting their learning spaces to support modern learning for all students"
ARC
Keywords: Classrooms -- Planning; School facilities -- Planning; School decoration; Architecture